An Early Indicator of Resistance in Barley to Russian Wheat Aphid. - Belefant-Miller, H. (1994)
During early stages of infestation by Russian wheat aphids (Diuraphis noxia [Mordvilko]; RWAs), barley (Hordeum vulgare L.) leaf cells collapsed and showed autofluorescence in the mesophyll and bundle sheath adjacent to the RWA stylet sheath. The response was visually similar to the hypersensitive cell death response, typical of resistance to microbial pathogens. Resistant barley produced significantly more collapsed, autofluorescent cells (CAC) than did susceptible barley. RWA stylet entry sites and sheath paths also fluoresced, making them easy to observe in whole leaf sections. The number of CAC increased with the number of RWAs and with the number of days of feeding in resistant plants. The CAC could be observed 1 d following infestation, making this the most rapid plant response toward the RWAs known to date. The response may be useful in screening for resistant plants and may provide insight into resistance mechanisms in barley.